Contentment Duration Mediates the Associations between Anxious Attachment Style and Psychological Distress - Ng, Sin Man; Hou, Wai Kai (Frontiers in Psychology, 2017)
Relatively little is known about the emotional processes underlying the association between adult attachment styles and psychological distress. This study aims to examine the role of contentment in terms of intensity and duration in the positive associations between anxious and avoidant attachment styles and psychological distress. A sample of 284 Chinese university students completed a self-reported questionnaire on attachment styles, intensity and duration of contentment, and anxiety and depressive symptoms. Structural equation modeling revealed that duration of contentment mediated the positive associations of anxious attachment style with anxiety symptoms [β = .05, p = .004; BC 95% CI (.02, .11)] and depressive symptoms [β = .04, p = .03; BC 95% CI (.003, .09)], model fit: χ2 (259) = 455.06, p < .001, CFI = .95, TLI = .94, RMSEA = .05, SRMR = .07. Participants with higher anxious attachment style were more likely to report shorter duration of contentment, which was, in turn, associated with higher anxiety and depressive symptoms. The results suggest a positive emotional pathway underlying the association between anxious attachment style and psychological distress. Implications based on the findings are discussed.